Model of the Impact of Knowledge Management, Innovation, and Competitiveness on the Performance of Technical Vocational Higher Education - Rizqa Ula Fahadha; Muhammad Syamsul Maárif; Budi Yulianto (International Enterprise Integration Association, 2026)
This research investigates the impact of knowledge management, competitiveness, and innovation on the performance of civil servant personnel within the Applied Undergraduate Program at T University. Driven by fluctuating performance outcomes (2018–2023) and the professionalism mandates of Law Number 5 of 2014, this study addresses a critical gap by analyzing the specific mediating mechanisms of performance in technical-vocational higher education. Using a census method, data were collected between August and October 2024 through interviews with assessors and managers, complemented by objective performance appraisals from 2023. Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS revealed that knowledge management significantly enhances innovation and competitiveness. Furthermore, innovation significantly drives personnel performance, whereas the direct effects of knowledge management and competitiveness were insignificant. Indirectly, knowledge management improves performance solely through innovation, acting as a mediator rather than through competitiveness. The novelty of this research lies in empirically demonstrating that, in highly regulated vocational education environments, knowledge assets translate into tangible performance only when strictly channeled through innovative practices. Theoretically, this extends the knowledge-based view by isolating innovation as the critical mediator for civil servant performance. Practically, university administrators and policymakers must prioritize knowledge-sharing initiatives that directly stimulate innovation to meet academic and bureaucratic targets, rather than focusing primarily on individual competitiveness.